Republic of Slovenia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper discusses several features of the Slovene economy that may explain the weak relationship between credit and domestic demand growth. It reviews credit growth developments in Slovenia and in selected European Union new member states, and compares their experiences with that of noncore euro area countries, including Ireland, Greece, Portugal, and Spain, before their adoption of the euro. Findings on the relationships between credit and domestic demand based on simple correlation and regression analyses are also presented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet